Slutspil: Verdens ende og Cormac McCarthys dobbelte slutninger - Rye Andersen, Tore (Passage - Tidsskrift for litteratur og kritik, 2023)
The article begins with a close reading of the concluding passage of Cormac McCarthy’s novel The Road (2006), which depicts a postcatastrophic and anthropocentic scenario where the planet is destroyed beyond repair. The article then analyzes the rest of The Road, which on several levels is a novel about endings, and in dialogue with theories by for instance Frank Kermode, Peter Brooks, J. Hillis Miller and Marianna Torgovnick, it concludes by discussing McCarthy’s predilection for double endings, where the conclusion of the plot and the conclusion of the novel are not the same.